Infinite jest : a novel - Wallace, David Foster (Back Bay Books, 2006)
A spoof on our culture featuring a drug-and-alcohol rehabilitation house near Boston. The center becomes a hotbed of revolutionary activity by Quebec separatists in revolt against the Organization of North American Nations which now rules the continent.